Pengaruh Independensi, Keahlian Auditor, dan Pengalaman Auditor terhadap Audit Judgment: Studi Empiris pada BPK RI Perwakilan Provinsi Sumatera Barat - Annisa Tiara Rahim; Erinos NR (Jurnal Eksplorasi Akuntansi, 2024)
The aim of this research is to evaluate how the independence, expertise, and experience of auditors influence the audit evaluation process. The main focus of this study is the entire group of auditors working at the Representative Office of the Republic of Indonesia for the West Sumatra Province. As the total population is less than 100 individuals, the method of total sampling is employed, involving all members of the population as participants in the study. Consequently, the sample for this research consists of around 60 auditors from the Republic of Indonesia's BPK Representative Office for West Sumatra Province. The data for this research are collected through the distribution of a questionnaire.